Involvement of central nervous system in diabetes mellitus. - Verma, A (1984)
Brainstem auditory evoked responses were recorded in 22 diabetic patients with a variable duration of illness (mean 5.8 years) and 14 normal healthy controls of comparable age. The initial 10 millisecond components, found to be most consistent and reproducible, were analysed. Variations in the form of individual wave latency, interpeak latencies and V wave amplitude were compared in both the groups. No difference was found in any of the parameters. It was concluded that central neural pathways are not involved at least initially in diabetes mellitus.